Indentation creep behavior of Fe-8Ni-xZr oxide dispersion strengthened alloys - Tekin, Mustafa; Muhaffel, Faiz; Kotan, Hasan; Baydogan, Murat (Walter De Gruyter Gmbh, 2023)
This study was conducted to understand the creep behavior of two oxide dispersion strengthened alloys containing Zr as the alloying addition by performing indentation creep tests at room temperature. The oxide dispersion strengthened alloys were Fe-8Ni-xZr (x = 1 and 4 at.%, i.e., Zr-1 and Zr-4 alloys, respectively), which had been previously fabricated by mechanical alloying; followed by consolidation via equal channel angular extrusion at 1000?. The indentation tests were conducted under a maximum load of 100 mN with the loading rates at 300 and 400 mN min(-1). The hardness was calculated by the Oliver-Pharr method, and the creep properties, such as the creep displacement, creep strain rate, creep stress, and stress exponent n, were determined. The results showed that the Zr-4 alloy was harder than the Zr-1 alloy. However, the creep resistance of the Zr-1 alloy was better than that of the Zr-4 alloy. It was further demonstrated that both the hardness and creep resistance depended on the loading rate. Moreover, a possible creep mechanism was proposed. Although the tests were performed at room temperature, they can provide insight into the effect of an oxide dispersion strengthened alloys microstructure on creep at higher temperatures.
Keywords: creep mechanism; equal channel angular extrusion; indentation creep; oxide dispersion strengthened alloys; powder metallurgy; Zr content